Education, Economic Growth & Poverty Rate in Nigeria: Any Nexus? - Ehigiamusoe, Ehigiamusoe (Journal of Social and Development Sciences, 2013)
Education is seen as a veritable tool for the socio-political and economic emancipation of any country from the shackles of ignorance, poverty, unemployment and low economic growth. But despite the enormous increase in education expenditure and literacy rate in Nigeria in the past two decades, noninclusive growth and high poverty rate still permeate all facets of human endeavour. In this light, the paper examines the interrelationships among education, economic growth and poverty in Nigeria. The study adopts econometrics methodology as the analytical tool using secondary data from 1980-2012. Evidence from the study suggests that though a long-run relationship exists among education, economic growth and poverty rate in Nigeria, but neither total education expenditure nor literacy rate cause changes in poverty rate in Nigeria. While government expenditure on education was found to have a positive and significant impact on economic growth (both in the short-run and in the long-run), literacy rate has positive but insignificant impact on growth. This could be due to high rate of unemployed school leavers, weak institutional mechanism, obsolete school curricula, shortage of critical infrastructure, and brain drain syndrome which characterize the country. The paper therefore recommended an increase in budgetary allocation to education as well as a review of the school curricula with a view to making the educational system more responsive to growth and poverty reduction in Nigeria. Government should also create the enabling environment for the creation of jobs through the provision of critical infrastructure which accelerate the development of small scale enterprises. This will provide gainful employment for school leavers and make them contribute more to inclusive growth and poverty reduction in Nigeria.